An In-depth Examination of the Role and Dynamics of Presidential Institutions in Contemporary Political Systems - Haskar, Edi (Asosiasi Ide Bahasa Kepri, 2023)
The institution of the presidency plays a central role in the political systems of many countries around the world. This abstract aims to conduct an in-depth review of the role and dynamics of the presidential institution in the context of the contemporary political system. Through a descriptive and comparative analysis approach, this article explores a number of key aspects related to the presidential institution, including executive power, relations with legislative institutions, role in policy formation, and interactions with civil society. This research highlights variations in the structure and function of presidential institutions in different countries, as well as their impact on political stability, democracy and national development. By analyzing various case studies and related literature, this article seeks to provide a deeper understanding of the complexity and relevance of the presidential institution in the contemporary political context.